'Casual Friday'. (28th April 2023) - Ohta, Amy Snyder
Abstract : There is increasing research literature on instructional pragmatics, including work on Japanese, but little research on naturally occurring classroom innovations. This article presents a study of an instructional innovation called Casual Friday, where the professor of a university multi-section advanced-beginning (2nd year) Japanese language course designated certain lessons as spaces for graduate student teaching assistants (TAs) to involve students in using Japanese casual register. Analysis of interviews with instructional staff, student survey results, and classroom and meeting observations, shows how Casual Friday, an organizational transformation of the course, transformed activity systems (Engeström, 1987, 1999, 2003). Transformed TA roles created a pedagogical safe house (Canagarajah, 2004; Pomerantz and Bell, 2011; Pratt, 1991) on Casual Fridays by providing TAs instructional autonomy, stronger horizontal connections with students, and temporary freedom from the restraints of the course-as-usual. The re-organization thus promoted TA innovation, as they creatively used language, designed materials, taught dialect, introduced Japanese youth culture, etc. Triangulation with student surveys confirms findings of the interviews and observations, while also showing that students reported languaculture learning. Results suggest the benefits of carving out spaces within normally textbook-and-grammar-focused courses for TAs to have free rein in presenting and involving students with languaculture.